Морфологічні особливості формування крон бука лісового в молодому віці - Делеган, І.І. (Фактори експериментальної еволюції організмів, 2014)
Aims. Studies of the formation of the crown to determine the economic impact on measures for marketable quality wood. Methods. Forms crowns beech forest at a young age was determined by the method of A. Roloff (1986). Results. Results of the study of geographical beech crops on Roztotchya indicate that the predominant form of rod is Crown. According tendencies apical growth of trees studied ecotypes classified into three groups. The research method of branching axial shoot and lateral distance of the location of the first buds of the growth in European beech trees in geographical cultures in Roztotchya found that the formation of a beech tree crown essentially depends on the type of shoot branching axial and lateral placement of the first bud. Conclusions. To form the inventory of beech stands proposed a number of forest management in the creation of forest plantations and during the Сutting.

Key words: beech, forming the crown.